2000
DOI: 10.1053/jlts.2000.18507
|View full text |Cite
|
Sign up to set email alerts
|

Changing strategies in diagnosis and management of hilar cholangiocarcinoma

Abstract: Hilar cholangiocarcinoma is one of the most difficult tumors to stage and treat. This study aims to evaluate (1) the best diagnostic imaging, (2) the usefulness of preoperative biliary drainage, (3) the resectability rate, and (4) the results of palliative treatments and surgical resection. Seventy-six patients with hilar cholangiocarcinoma with a mean age of 64 ؎ 11 years were treated at our institution from 1989 to 1999. Patients were studied preoperatively using ultrasound, computed tomography (CT), and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 23 publications
(32 reference statements)
1
48
1
5
Order By: Relevance
“…Therefore, imaging also plays an important role in determining whether a patient is a candidate for curative resection and in planning management [16]. Helical CT and MRCP are the best imaging techniques to diagnose the disease, delineate the extent of the tumor and rule out liver metastasis and enlarged lymph nodes [17]. MDCT allows for faster scanning with thinner collimation and can result in an improved diagnosis and evaluation of hilar cholangiocarcinoma [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, imaging also plays an important role in determining whether a patient is a candidate for curative resection and in planning management [16]. Helical CT and MRCP are the best imaging techniques to diagnose the disease, delineate the extent of the tumor and rule out liver metastasis and enlarged lymph nodes [17]. MDCT allows for faster scanning with thinner collimation and can result in an improved diagnosis and evaluation of hilar cholangiocarcinoma [15].…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates after surgical resection are better than those after palliative treatment and were reported to be 45-87% at 1 year, 21-30% at 3 years, and 11-21% at 5 years. [2][3][4][5] However, curative surgical resection can be performed in only 30 -40% of patients with hilar duct carcinoma, even in recent reports. 2,5 Patients with unresectable hilar duct carcinomas often are treated by biliary drainage with or without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Despite recent advances in diagnostic and therapeutic technologies, patients with carcinoma of the hepatic hilar duct are often diagnosed in the advanced stage and the majority (approximately 58 -83%) of patients can only be treated palliatively. [1][2][3][4][5][6][7] The reported median survival time for patients with unresectable hilar duct carcinoma ranges from 3 to 11 months. nal beam radiotherapy (EBRT) alone or in combination with brachytherapy, 10 -12 but others reported that EBRT had no apparent effect on either survival or late toxicity.…”
mentioning
confidence: 99%
“…Studies revealed that patients receiving surgical treatment have a longer survival and better quality of life compared to the patients underwent nonsurgical palliative therapies [12,13]. Despite main advantages of surgical bypass, high early postoperative morbidity and mortality and complications due to external biliary drainage such as fluid and electrolyte imbalance, loss of bile, dislocation and obstruction of external catheter have to be considered [14,15].…”
Section: Introductionmentioning
confidence: 99%